Pengaruh Kepemimpinan dan Lingkungan Kerja Non Fisik Terhadap Kinerja Karyawan di PT. Maan Ghodaqo Shiddiq Lestari Jombang - Uzlifatul Mufidah (BIMA : Journal of Business and Innovation Management, 2019)
Aims to analyze the influence og leadership and non Physical work environment on employee performance, both patially and simultaneosly on emplyee performance. This reserch is categorized as quantitative research using questionnaries as instruments. The population in this study were employees at PT. Maan Ghodaqqo Shiddiq Lestari Jombang. Samples taken as many 75 respondents were determined by sampling technique, and the analysis used was multiple regression. This results of this study indicate that ( 1) Leadership has a significant effect on performance. This can be seen from the t test of 2,833 with a significance value of 0,006 (2) Non Physical work enviretmen dose ot have a partial effect obtained t count=1,337>0,2272 with a significance value of 0,185. (3) Leadership and non phsical work environment influence employee performance with F count 5,111> F table value and significant value 0,008.